2007
DOI: 10.1039/b712290j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient asymmetric reduction of arylpropionic aldehydes by Horse Liver Alcohol Dehydrogenase through dynamic kinetic resolution

Abstract: The enantioselective synthesis of (2S)-2-phenylpropanol and (2S)-2-(4-iso-butylphenyl)propanol ((S)-Ibuprofenol) has been achieved by means of Horse Liver Alcohol Dehydrogenase (HLADH) in buffered aqueous solution or buffered organic solvent mixtures; under the reaction conditions, a dynamic kinetic resolution (DKR) process was realized with good reaction yields and enantiomeric ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…[67] Giacomini and coworkers, found that HLADH could effect the reduction of 2-phenylpropanal to ( S )-2-phenylpropanol in 99% ee. Similar results were obtained for ibuprofenal.…”
Section: Other β-Keto-systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[67] Giacomini and coworkers, found that HLADH could effect the reduction of 2-phenylpropanal to ( S )-2-phenylpropanol in 99% ee. Similar results were obtained for ibuprofenal.…”
Section: Other β-Keto-systemsmentioning
confidence: 99%
“…This α‐alkyl aldehyde‐variant of the DYRKR has been implemented in the stereoselective reduction of profenals in two laboratories recently 67. Giacomini and co‐workers, found that HLADH could effect the reduction of 2‐phenylpropanal to ( S )‐2‐phenylpropanol in 99% ee .…”
Section: Other β‐Keto Systemsmentioning
confidence: 99%
“…Herein, we have highlighted the potential of the biocatalytic disproportionation reaction of aldehydes for the generation of non‐racemic prim alcohols and α‐chiral carboxylic acids (“profens”)25, 26 in equimolar amounts through a redox‐neutral process in which the substrates are advantageously not limited to non‐enolizable aldehydes. The exploitation of the asymmetric variant of the biocatalytic Cannizzaro‐type reaction is currently underway in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…8 Asymmetric reduction of the prochiral ketones using ADH is an important tool for industrial production of enantiopure alcohols. [9][10] Additionally, ADHs can accomplish dynamic kinetic resolution, [11][12] and deracemization of racemic alcohols [13][14] as well as racemization of enantiopure alcohols, [15][16] processes by which high yields (theoretically up to 100 %) of a single enantiomer can be obtained. Although several ADHs have been identified from various organisms, their substrate scope tends to be limited and mutagenesis has often been necessary to expand the range of substrates.…”
Section: Fig 1 Examples Of Drugs Derived From Chiral Aromatic Secondmentioning
confidence: 99%